Incidencia y análisis de factores asociados a cefalea post raquídea en pacientes sometidos a cirugía electiva en el Hospital Regional de Loreto, 2025 - Bustamante Neyra, Fanyo Jhonattan (2025)
The study aims to determine the incidence and factors associated with post-spinal headache (CPR) in patients undergoing elective surgery at the Loreto Regional Hospital during the year 2025. A retrospective, cross-sectional and correlational design is proposed, through the review of 73 medical records and anesthesia sheets of patients over 18 years of age undergoing spinal anesthesia. Incomplete records, cases with previous neurological pathologies, surgical reinterventions, emergency surgeries, and those undergoing general anesthesia were excluded. Data collection will be carried out through a structured file in digital format, which will record anesthetic variables (size and type of needle, number of puncture attempts), clinical variables (age, sex, body mass index, history of headache) and operative variables (early mobilization). The data will be processed in SPSS v25, using descriptive and inferential statistics. The dependent variable will be the presence or absence of CPR, for which logistic regression and calculation of Odds Ratio will be applied in bivariate analysis with significance p < 0.05. In conclusion, this study will allow estimating the incidence of CPR and exploring associated factors in the operated population, generating useful evidence for the prevention and improvement of anesthetic safety at the Regional Hospital of Loreto.